Influence of defective bone marrow osteogenesis on fracture repair in an experimental model of senile osteoporosis - Egermann, Marcus; Heil, Petra; Tami, Andrea; Ito, Keita; Janicki, Patricia; Von Rechenberg, Brigitte; Hofstetter, Willy; Richards, Peter J. (Journal of orthopaedic research, 2010)
Bone marrow osteogenesis in senile osteoporotic bone is impaired and, as such, may have significant implications on the successful outcome of fracture repair. Here we utilize a well-established murine model of senile osteoporosis, the P6 strain of senescence-accelerated mice (SAMP6), to investigate fracture healing in aged osteoporotic bone. A femoral osteotomy was created in SAMP6 and in non-osteoporotic age-matched control R1 senescence-resistant mice (SAMR1). The course of fracture healing was evaluated over a period of 42 days using quantitative µCT and histological analysis. The differentiation capabilities of bone mesenchymal progenitor cells derived from SAMP6 and SAMR1 mice was examined, and their osteogenic potential determined. Although preliminary in vitro analysis confirmed that bone marrow-derived stem cells (BMSC) isolated from SAMP6 mice had a reduced osteogenic capacity, no significant deficit in fracture repair as determined by quantitative µCT could be detected. This was supported by histology assessment, where complete bridging of the fracture gap was evident by day 28 and was fully healed day 42 in both SAMP6 and SAMR1 mice. Further in vitro studies revealed that periosteal-derived progenitor cells (PDPC) isolated from SAMP6 mice had an osteogenic potential comparable to that observed in SAMR1 mice. In conclusion, fracture healing in SAMP6 mice is not detrimentally affected by impairment of BMSC osteogenesis, suggesting that bone marrow-mediated repair processes are dispensable for normal bone healing in this senile osteoporotic fracture model. Furthermore, the influence of PDPC in the repair process may partly explain the absence of any detectable deficits in fracture repair in SAMP6 mice.